Hydrodynamic Model and Tidal Current Energy Potential in Lepar Strait, Indonesia - Harman Ajiwibowo; Munawir Bintang Pratama (International Journal of Renewable Energy Development, 2022)
Previous studies have shown the abundance of tidal energy resources in Indonesia. However, some sites have yet to be considered. The Lepar Strait, for example, is located between Bangka and Lepar Islands. This paper describes a field survey and numerical modelling conducted in the Lepar Strait. The modelling was performed using Delft3D, with the aim of determining potential sites for harvesting tidal current energy and estimate the generated power. In the modelling, the domain decomposition method was employed for model downscaling, allowing grid resolution reaching 130 x 130 m2, which is sufficient to represent the narrow gaps between tiny islands in the area of interest. The National Bathymetric (Batnas) from the Geospatial Information Agency (BIG) and the International Hydrographic Organization (IHO) tide constituents were applied for the bathymetry and tide elevation boundaries. The comparison between the surveyed and modelled data showed a good agreement. The RMSE and r for water level are > 0.95 and < 0.15, and the RMSE for velocity was <0.19. Furthermore, an energetic flow reaching 1.5 m/s was found at the Northern part of Lepar Strait, situated at the narrow gaps. The Gorlov Helical Turbine was selected in this study due to shallow water and low mean velocity. In the 2019 model, the power density and power output at the best potential sites were 2,436.94 kWh/m2 and 1,870.41 kWh, respectively. This number is higher than those previously found in Kelabat Bay. Nonetheless, it is still far below the currently promising project in Larantuka and Lombok Straits. Future research is recommended, to conduct a detailed field measurement campaign and assess the impact of energy extraction in more detail.